Welfare Reform, Insurance Coverage Pre-Pregnancy, and Timely Enrollment: An Eight-State Study - E. Kathleen Adams; Norma I. Gavin; Willard G. Manning; Arden Handler (SAGE Publishing, 2005)
Implementation of the Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) broke the automatic linkage between Medicaid eligibility/enrollment and welfare cash assistance for women eligible at welfare income levels. This study used data from the Pregnancy Risk Assessment Monitoring System (PRAMS) for the period 1996-1999 to examine insurance coverage of these and other pregnant women pre- and post-PRWORA. Controlling for individual characteristics and economic growth, the relative odds of having private insurance did not change while the odds of being Medicaid enrolled versus uninsured pre-pregnancy declined for welfare-eligible women post-PRWORA. The absolute effect was a decline of 7.9 percentage points in the probability of welfare-eligible women being insured. While these results apply to the early years of welfare reform, it is still likely that states can improve Medicaid outreach and enrollment of women eligible prior to pregnancy.